Mfn2 Regulates High Glucose-Induced MAMs Dysfunction and Apoptosis in Podocytes via PERK Pathway - Cao, Yun; Chen, Zhaowei; Hu, Jijia; Feng, Jun; Zhu, Zijing; Fan, Yanqin; Lin, Qiaoxuan; Ding, Guohua (Frontiers in Cell and Developmental Biology, 2021)
The endoplasmic reticulum stress (ERS) and mitochondrial dysfunction in high glucose (HG)-induced podocyte injury have been demonstrated to the progression of diabetic kidney disease (DKD), however, the pathological mechanisms remain equivocal. Mitofusin2 (Mfn2) was initially identified as a dynamin-like protein involved in fusing the outer mitochondrial membrane (OMM). More recently, Mfn2 has been reported to be located at the endoplasmic reticulum (ER) membranes that contact OMM. Mitochondria-associated ER membranes (MAMs) is the intercellular membrane subdomain, which connects the mitochondria and ER through a proteinaceous tether. Here, we observed the suppression of Mfn2 expression in the glomeruli and glomerular podocytes of patients with DKD. Streptozotocin (STZ)-induced diabetic rats exhibited abnormal mitochondrial morphology and MAMs reduction in podocytes, accompanied by decreased expression of Mfn2 and activation of all three unfolded protein response (UPR) pathways (IRE1, ATF6, and PERK). The HG-induced mitochondrial dysfunction, MAMs reduction, and increased apoptosis in-vitro were accompanied by the downregulation of Mfn2 and activation of the PERK pathway. Mfn2 physically interacts with PERK, and HG promotes a decrease in Mfn2-PERK interaction. In addition, Mfn2-silenced podocytes showed mitochondrial dysfunction, MAMs reduction, activation of PERK pathway, and increased apoptosis. Conversely, all these effects of HG stimulation were alleviated significantly by Mfn2 overexpression. Furthermore, the inhibition of PERK phosphorylation protected mitochondrial functions but did not affect the expression of Mfn2 in HG-treated podocytes. Therefore, this study confirmed that Mfn2 regulates the morphology and functions of MAMs and mitochondria, and exerts anti-apoptotic effects on podocytes by inhibiting the PERK pathway. Hence, the Mfn2-PERK signaling pathway may be a new therapeutic target for preventing podocyte injury in DKD.